Women and monastic reform in the Medieval West, c. 1000-1500: debating identities, creating communities - Hotchin, Julie; Thibaut, Jirki (Studies in the History of Medieval Religion Ser., 2023)
New approaches to understanding religious women's involvement in monastic reform, demonstrating how women's experiences were more ambiguous and multi-layered than previously assumed.